On SARS Type Economic Effects During Infectious Disease Outbreaks - Brahmbhatt, Milan 1996- (The World Bank, 2008)
Infectious disease outbreaks can exact a high human and economic cost through illness and death. But, as with severe acute respiratory syndrome (SARS) in East Asia in 2003, or the plague outbreak in Surat, India, in 1994, they can also create severe economic disruptions even when there is, ultimately, relatively little illness or death. Such disruptions are commonly the result of uncoordinated and panicky efforts by individuals to avoid becoming infected, of preventive activity. This paper places these "SARS type" effects in the context of research on economic epidemiology, in which behavioral responses to disease risk have both economic and epidemiological consequences. The paper looks in particular at how people form subjective probability judgments about disease risk. Public opinion surveys during the SARS outbreak provide suggestive evidence that people did indeed at times hold excessively high perceptions of the risk of becoming infected, or, if infected, of dying from the disease. The paper discusses research in behavioral economics and the theory of information cascades that may shed light on the origin of such biases. The authors consider whether public information strategies can help reduce unwarranted panic. A preliminary question is why governments often seem to have strong incentives to conceal information about infectious disease outbreaks. The paper reviews recent game-theoretic analysis that clarifies government incentives. An important finding is that government incentives to conceal decline the more numerous are non-official sources of information about a possible disease outbreak. The findings suggest that honesty may indeed be the best public policy under modern conditions of easy mass global communications